Comparative evaluation of antifungal susceptibility testing methods for Rhizopus species isolates - Mohd Saqib Hasan; Prashant Gupta; Gopa Banerjee (Current Medical Mycology)
Background and Purpose:The mainstay of treatment for COVID-19-associated mucormycosis was liposomal Amphotericin B. Other antifungal agents such as posaconazole and isavuconazole were also used. CLSI M38 A3 and EUCAST recommend broth microdilution method for Antifungal susceptibility testing. We, therefore, conducted this study to see what potency and zone diameters correlate with the gold standard broth microdilution method.Materials and Methods: All the isolates were identified by MALDI-TOF. A total of 127 isolates of 83 Rhizopus oryzae complex and 44 isolates of Rhizopus microsporus complex were selected. Anti-fungal susceptibility testing by Disc diffusion and E-test was done on non-supplemented Mueller Hinton Agar and was compared with the CLSI broth microdilution method of Anti-fungal susceptibility testing.Results: Percentage agreement was found to be more in the case of the E test than Disc Diffusion method. In the case of Rhizopus oryzae, posaconazole had 98.79% agreement with broth microdilution followed by Isavuconazole (97.59%), Itraconazole (96.38%), and Amphotericin B (91.56%). Conclusion: Disc diffusion correlates well with broth microdilution (BMD), although its correlation is weaker when compared to the E test. The effective concentration of AMB discs for antifungal susceptibility testing (AFST) depends on the specific Rhizopus species.